OP0181 Prediction of Flare after Stopping TNF-Inhibitor by Baseline Ultrasonography and Patient Characteristics in Rheumatoid Arthritis Patients with Low Disease Activity: 12-Month Results. (15th July 2016) - Lamers-Karnebeek, F.B.G.; Luime, J.; van Riel, P.; Jacobs, J.; Jansen, T.
Abstract : Background: A significant number of rheumatoid arthritis (RA) patients can reach low disease activity (LDA) by using TNF-inhibitors (TNF-i), but this therapy can cause serious side-effects and is expensive. Therefore it could be expedient to stop in case of LDA, unless a relapse can be predicted. Ultrasonography of joints seems to be a predictor in this respect in smaller studies. The Dutch POET (Potential Optimalisation of Expediency of TNF-i (TNF-inhibitor)) study, is a multicenter randomized prospective cohort study investigating if in patients with RA with LDA on TNF-i and conventional DMARD, the TNF-i can be stopped. Patients were randomized to continue or stop TNF-i. Part of this study is the POET-ultrasonography (US) study. Objectives: To investigate whether US, at the time of stopping TNF-i in RA patients with LDA, is an additive predictor for flare besides clinical data. Methods: Data were analysed of 251 patients who stopped TNF-i in the POET study. Participating patients had RA according to ACR 1987 criteria, >6 months a DAS28 <3.2 (LDA) and treatment with TNF-i >1 year next to a conventional DMARD, with no dose change 6 months prior to randomisation. Nineteen trained ultrasonographers performed at baseline of the study US (with different US machines) of 20 joints: MCP 1–5 dorsal and volar, wrist and MTP 2–5 dorsal aspect, all bilaterally. The joints were graded on grayscale (GS; 0–3) and power Doppler (PD; 0–3). US signs of arthritis were defined as GS>1 and/or PD>0. Trial visits were performed every 3 months during 12 months and intercurrently when flare was suspected. Flare was defined as DAS28 >3.2 and at least >0.6 increase compared to the baseline DAS28. Univariate and multivariate Cox-regression was performed guided by clinical factors described in the literature and US. Results: The Kaplan Meier curve for patients with US signs of arthritis in one or more joints shows greater/higher risk of flare and shorter relapse-free period compared to the curve for patients without US signs of arthritis, p= (figure ). At multivariate analysis (table), correcting for potentially clinical predictors, US detected arthritis stayed a statistically significant predictor of flare; HR 1.69; 95% CI 1.11 to 2.53. The predictive value of US seems not that strong that it can be used in individual patients. Conclusions: The presence of US arthritis is associated with an earlier flare and a higher flare rate compared to those with negative US taking into account demographic and clinical patient characteristics. Disclosure of Interest: F. Lamers-Karnebeek Grant/research support from: Abbvie, J. Luime: None declared, P. van Riel: None declared, J. Jacobs: None declared, T. Jansen: None declared